Effects of Helicobacter pylori Infection on the Histology, Cellular Phenotype, K-ras Mutations, and Cell Kinetics in Gastric Intestinal Metaplasia in Patients with Chronic Gastritis and Gastric Cancer - Watari, Jiro; Tanabe, Hiroki; Moriichi, Kentaro; Fujiya, Mikihiro; Amenta, Peter S.; Miwa, Hiroto; Kohgo, Yutaka; Das, Kiron M. (IntechOpen, 2011)
None